PENGARUH FASILITAS LABORATORIUM KOMPUTER TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN MYOB ACCOUNTING DI SMK KOSGORO PENAWARTAMA - siti nur azizah (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2022)
The computer laboratory was one of the learning facilities owned by the school to support subjects related to special learning rooms, for example in Spreadsheet or MYOB Accounting training courses and so on. Meanwhile, learning motivation were a supporting impetus to increase the enthusiasm and feelings of pleasure of students so that it create a passion for learning, in achieving a learning goal. The purpose of this study was to determine the effect of computer laboratory facilities on student motivation at SMK Kosgoro Penawartama. The collection technique used a questionnaire and observation, in this study the entire population of class XI Financial and Institutional Accounting was 32 students, the sample of this study were a population sample or census because the subject was less than 100 students, the entire population were used for the sample. It could be seen the results of this study 1) The results of the regression analysis of computer laboratory facilities on learning motivation with a significant value of tcount = 2,551 > ttable = 2,042 until Ha is accepted and Ho was rejected, meaning that there were an influence of computer laboratory facilities on learning motivation at SMK Kosgoro Penawartama. 2) The magnitude of the influence of computer laboratory facilities on learning motivation was 17,8% while the remaining 82,2% was influenced by other factors. 3) The influence of computer laboratory facilities on learning motivation was 0.4222 in the medium category, meaning that the computer laboratory facilities variable had a moderate level of relationship with the learning motivation variable.